High prevalence of multi-drug resistant Streptococcus pneumoniae among healthy children in Thailand - Rapee Thummeepak; Nontapat Leerach; Duangkamol Kunthalert; Udomsak Tangchaisuriya; Aunchalee Thanwisai; Sutthirat Sitthisak (Elsevier, 2015)
Summary: Antibiotic resistance in Streptococcus pneumoniae is an emerging health problem worldwide. The incidence of antimicrobial-resistant S. pneumoniae is increasing, and nasal colonization of S. pneumoniae in children increases the risk of pneumococcal infection. In this study, the prevalence of S. pneumoniae nasal colonization was studied in Thai children from three different districts. S. pneumoniae nasal colonization was found in 38 of 237 subjects (16.0%). The carriage rate indicated higher rates in two rural districts (18.2% and 29.8%) than in the urban district (2.8%). The antibiotic susceptibility pattern was determined using the disk diffusion method. Prevalence of multi-drug resistance S. pneumoniae (MDR-SP) was 31.6%. Resistance to commonly prescribed antibiotics was found for ampicillin (5.3%), azithromycin (26.3%), cefepime (2.6%), chloramphenicol (18.4%), clindamycin (18.4%), erythromycin (21.1%), oxacillin (44.7%), trimethoprim/sulfamethoxazole (78.9%) and tetracycline (15.8%). All isolates were sensitive to ceftriaxone. The pulsed-field gel electrophoresis pattern was used to compare genetic diversity of the S. pneumoniae isolates. PFGE demonstrated the variation in genotypes of S. pneumoniae from different areas. High prevalence of multi-drug resistance S. pneumoniae nasal colonization in healthy Thai children was indicated. Effective strategies for appropriate use of antibiotics are therefore needed in the community. Keywords: Antibacterial resistance, Streptococcus pneumoniae, Genotype, Children, Nasal colonization